Integrasi Nilai-Nilai Islami dan Penguatan Pendidikan Karakter dalam Pembentukan Sikap Prososial Berbasis Tri Sentra pada Anak Usia Dini di TK Negeri Pembina Kecamatan Gringsing Kabupaten Batang - Mufidah, Diina (CV. Supernova Office Stationary and Printing, 2022)
Character education needs to be developed from an early age starting from kindergarten. However, there is a need for a development model that is in accordance with the level of early childhood development. This study aims to analyze the integration of Islamic values ??and strengthen character education in the formation of tri-centra-based prosocial attitudes in early childhood at Pembina State Kindergarten, Gringsing District, Batang Regency. This research is included in qualitative research with a phenomenological approach. Based on the research, it shows that the integration of Islamic values ??and strengthening character education in the formation of tri-centra-based prosocial attitudes in Early Childhood at Pembina State Kindergarten, goes according to school programs that have been implemented thanks to the cooperation of schools and parents. Barriers to the integration of Islamic values ??and strengthening character education in the formation of tri-centra-based prosocial attitudes in Early Childhood at Pembina State Kindergarten, among others: First, parents as role models and provide insight for children must understand and understand character education which is not only applied in schools but also at home so that the process of implementing character education is in accordance with the programs implemented in schools. Second, early childhood, there are children who have a slow or different grasping power, children who are used to and are not accustomed to adapting to their environment and have not been able to develop a strong sense of self-confidence, these children need support from those closest to them such as people parents and teachers.